2023
DOI: 10.7759/cureus.38915
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Timing of Laparoscopic Cholecystectomy in Acute Cholecystitis: A Single-Center Study

Abstract: Introduction Early laparoscopic cholecystectomy (ELC) is a treatment option for acute cholecystitis (AC). However, the timing of ELC is controversial. Delayed laparoscopic cholecystectomy (DLC) continues to be a common practice. This study aims to determine the optimal timing of ELC in AC. Materials and methods Patients who underwent surgery for AC between 2014 and 2020 were divided into three groups: immediate laparoscopic cholecystectomy (ILC), prolonged ELC (pELC), and DLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Early studies reported high mortality rates and bile duct injuries associated with LC [3]. However, as experience in laparoscopic surgery increased over the years, early laparoscopic cholecystectomy (ELC) has demonstrated superiority over delayed laparoscopic cholecystectomy, as it reduced hospital stays and had similar postoperative outcomes [4]. Currently, LC is considered the gold standard for treating AC [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies reported high mortality rates and bile duct injuries associated with LC [3]. However, as experience in laparoscopic surgery increased over the years, early laparoscopic cholecystectomy (ELC) has demonstrated superiority over delayed laparoscopic cholecystectomy, as it reduced hospital stays and had similar postoperative outcomes [4]. Currently, LC is considered the gold standard for treating AC [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 Pearson Chi-Square test,2 Student t-test,3 Mann Whitney U test,4 Fisher's exact test, * p<0.05 significance, CCI: Charlson comorbidity index, ASA: American Society of Anesthesiologists, WBC: White blood cell, CRP: C-reactive protein, AST: Aspartate aminotransferase, ALT: Alanine aminotransferase, ALP: Alkaline phosphatase, GGT: Gamma-glutamyl transferase, TBIL: Total bilirubin, DBIL: Direct bilirubin, GB: Gallbladder…”
mentioning
confidence: 99%